Mitigations of flooding and soil erosions Geo-Disasters in Thailand and Laos due to climate change: From Mountains to Lowlands - D. T. Bergado; S. Chaiyaput; P. Voottipruex; T. Hino; N. Chanmee (International Association of Lowland Technology, 2017)
In 2011, Thailand has suffered from devastating flooding due to climate change. During this time, 2 typhoons from the Pacific area went straight across Vietnam to Northern Laos and Northern Thailand instead of the usual path to Taiwan and Japan. Subsequently, huge flooding damaged many infrastructures and overtopped flood protection dikes of many industrial estates and educational institutions in the Central Plain of Thailand such as at Hi-Tech Industrial Estate, Bang Pa- In Industrial Estate, Navanakorn Industrial Estate and Asian Institute of Technology, to name a few. The same phenomenon also occurred in neighboring Laos PDR which caused unusually heavy rains and widespread river flooding. Consequently, riverbank erosions accompanied by slope failures occurred at Xedon River in Pakse, Southern Laos due to saturation caused by high water levels accompanied by high velocity flow of the flooded river. To evaluate the stability of these mitigation structures, finite element and limit equilibrium methods were utilized. PLAXIS 2D software was used to analyze the slope protection schemes at low and high water levels incorporating the various supporting and reinforcing materials. Moreover, the PLAXIS 2D software was also utilized to predict the vertical deformations of improved flood control dikes with increased embankment height at different cases of flood water levels. In addition, the SLIDE software was used to predict the factor of safety by using limit equilibrium method for the various riverbank erosion protection structures. Furthermore, RESSA software was utilized to evaluate the slope stability of the erosion protection structures with geosynthetic reinforcements of Xedon riverbank in Pakse combined with gabions and mattresses. Laos PDR is mountainous with high elevations.